Numerical analysis on the behaviour of cfrp shear- strengthened rc deep beams with large square and circular openings - Shim, Chee Wei (2015)
This study presents a finite element analysis to investigate the behaviour of reinforced concrete deep beams with square and circular openings. Deep beams are always constructed at the lower floors as transfer beams to transfer the loads from the entire building to the foundations. Reinforced concrete (RC) acts as one of the most essential building materials and it is widely used in the construction due to its low pricing, efficiency and strength of the reinforced concretes as well as its stiffness. Openings are inevitable for the architectural and mechanical purpose to accommodate the conduits. However, presence of openings in the deep beams will significantly reduce the load capacity of the deep beams, as well as excessive cracking and deflection. Strengthening by Carbon Fibre Reinforced Polymer helps in regain the load bearing capacity of the deep beams. Researches were focus on the experimental work and hence this study conducted in terms of the numerical aspects and finite element analysis. ANSYS CivilFEM 12.0, a finite element modelling and analysis software, was used to analysis the deep beams. Three – dimensional modelling of RC deep beams was adopted in this study. A total of 14 beams including one control beam were modelled as simply supported beam with openings where the locations of the openings were at the support which was 300 mm from the edge of the beams. Two incremental loads were applied at the 800 mm from the edge of the beams. The beams was symmetrical in shape. The beams had the cross sections of 120 mm x 600 mm and 2400 mm in length with square and circular openings. The objectives of this study were to determine the most effective strengthening method by using CFRP in terms of load-deflection behaviours, crack patterns, stress and strain contours. This study was validated by experimental results. Various strengthening methods were used to identify the most effective method of strengthening which included orientation of CFRP in vertical alignment (90º), horizontal alignment (0º), whole piece, cut strips, surface strengthening and U-wrap strengthening. Deep beams with openings failed due to shear cracks because of the sharp edges of the openings. From the finding, the square opening and circular opening experienced a reduction of 62.0% and 51.3% in beam capacity, respectively. From the various strengthening configurations of CFRP, configuration with vertical alignment, whole piece and U-wrap strengthening method was the most effective method. CFRP restored the load bearing capacity with most effective method by 63.0% and 85.0% for deep beams with square and circular openings respectively. A comparison between the numerical and experiments results showed that a comparable agreement on the load deflection behaviours and strong agreement on the crack patterns.